Application for Marketplace Agricultural Product - Nugroho, Heru; Hendriyanto, Robbi; Tisamawi, Kautsar (IJAIT (International Journal of Applied Information Technology), 2018)
Farmers empowerment is an effort to improve farmers' ability to conduct better farming through education and training, counseling and mentoring, development of Agricultural products and marketing system, consolidation and guarantee agricultural land area, ease of access of science, technology and information, and institutional strengthening. Support Information Technology is not only making it easier regarding resources but become media marketing agricultural products for farmers in Indonesia. Currently, the chain of commerce for the sale of agricultural products is still very long. That causes the price of agricultural products is quite high. However, when the farmers sell the product, the hat price is still relatively low. To reduce the chain of commerce is needed a system that can provide information as well as a marketing place for agricultural products and can also use for direct purchase by consumers. The system that can meet those needs is e-commerce that built Marketplace based. Based on the findings of e-Marketer, the business to consumer (B2C) e-commerce market in Indonesia has the largest growth record in the Asia Pacific through 2017. There is potential to improve the welfare of farmers in Indonesia using information technology for marketing as well as direct transactions with consumers. In this paper will be proposed Android Application for Marketplace Agricultural Product Base Android. This Application will development by Software Development Life Cycle (SDLC) Prototype method with Java and XML programming languages and database management will be used MySQL. This Application will provide information on agricultural products, facilitate farmers to market their agricultural products, and facilitate farmers to conduct direct transactions with consumers.